Humanizing Digital Mental Health through Social Media: Centering Experiences of Gang-Involved Youth Exposed to High Rates of Violence. (August 2018) - Frey, William R
As the lives of young people expand further into digital spaces, our understandings of their expressions and language on social media become more consequential for providing individualized and applicable mental health resources. This holds true for young people exposed to high rates of community violence who may also lack access to health resources offline. Social media may provide insights into the impacts of community violence exposure on mental health. However, much of what is shared on social media contains localized language and context, which poses challenges regarding interpretation. In this perspective, I offer insights gained from the Beyond the Bullets: The Complexities and Ethical Challenges of Interpreting Social Media Posts workshop during the Digital Interventions in Mental Health conference in London, England: (1) social media as an underutilized environmental context in mental health services; (2) interpreting the meaning of social media posts is challenging, and there are additional challenges when users are exposed to offline violence and (3) the importance of having various perspectives when interpreting social media posts to build contextually nuanced and theoretically based understandings of digital social behavior.